Integrated pan-cancer analysis and experimental verification of the roles of tropomyosin 4 in gastric cancer - Guo, Qijing; Zhao, Linglin; Yan, Nan; Li, Yan; Guo, Cuiping; Dang, Shengyan; Shen, Xianliang; Han, Jianfang; Luo, Yushuang (Frontiers in Immunology, 2023)
Objective: To investigate the function of Tropomyosin 4 (TPM4) in a pan-cancer, especially in gastric cancer (GC) with comprehensive bioinformatics analysis and molecular experiments. Methods: We used UCSC Xena, The Cancer Genome Atlas(TCGA), Genotype-Tissue Expression Project(GTEx) TIMER2.0, GEPIA, cBioPortal, and UALCAN online websites and databases for the extraction of data on TPM4 in pan-cancer. TPM4 expression was investigated concerning the prognosis, genetic alterations, epigenetic alterations, and immune infiltration. RNA22, miRWalk, miRDB, Starbase 2.0, and Cytoscape were employed for identifying and constructing the regulatory network of lncRNA, miRNA, and TPM4 within GC. Data from GSCALite and drug bank databases were employed to analyze that TPM4 expression-related drugs sensitivity. Gene Ontology(GO), enrichment analyses of the Kyoto Encyclopedia of Genes and Genomes(KEGG), as well as wound healing assays and transwell experiments (Matrigel )were employed to investigate the biological functions of TPM4 within GC. Result: Comprehensive pan-cancer analysis revealed that TPM4 has a certain diagnostic and prognosis value in most cancers. Alterations of the TPM4, including duplications and deep mutations, and epigenetic alterations revealed that TPM4 expression is related to DNA methylation inhibitors as well as RNA methylation regulators at high concentrations. Besides, TPM4 expression was correlated with immune cell infiltration, and immune checkpoint (ICP) gene expression, the tumor mutational burden(TMB), microsatellite instability(MSI), as well as neoantigens (NEO) influence its response to immunotherapy. A lncRNA-miRNA -TPM4 network regulated GC development and progression. TPM4 expression was related to docetaxel and 5-fluorouracil sensitivity. Gene function enrichment analyses showed that genes co-expressed with TPM4 were enriched within the extracellular matrix (ECM)-related pathways. Wound-healing and (Matrigel) transwell assays revealed that TPM4 promotes cell migration and invasion. TPM4, as an oncogene, plays a biological role, perhaps via ECM remodeling in GC. Conclusions: TPM4 is a prospective diagnostic marker for the diagnosis, treatment outcome, immunology and chemotherapy for the treatment of pan-cancer, including GC. The lncRNA-miRNA-TPM4 network regulates the mechanism of GC progress.TPM4 may facilitate the invasion and migration of GC cells, possibly through ECM remodeling.